CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE DURING ECONOMIC CRISES: A GLOBAL EVIDENCE - Botutihe, Nur'atni (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Corporate governance (CG) is an important element in ensuring accountability and operational efficiency, especially during global economic crises such as the 2008 financial crisis and the COVID-19 pandemic. Although many studies have discussed the relationship between CG and financial performance (FP), few have explicitly considered the institutional context across countries. This gap suggests the need to examine how institutional factors moderate the relationship between CG and FP during times of crisis.This study examines how CG mechanisms affect corporate financial performance during economic crises, highlighting the moderating role of differences in institutional settings across countries. A narrative review approach is used to synthesize conceptual and empirical findings from reputable journals (2000–2024), focusing on two major crises: the 2008 global crisis and the COVID-19 pandemic. The literature is mapped by theme, geographic region, and type of crisis.The results show that strong CG mechanisms, such as board independence and the existence of an audit committee, can improve financial resilience during crises. However, their effectiveness varies greatly depending on the quality of institutions in each country. In countries with weak institutions, formal CG structures often do not produce optimal results. These findings underscore the complexity of the CG–FP relationship and the importance of contextual strategies.In conclusion, CG plays an important role in maintaining corporate financial stability during crises, but its impact is highly dependent on the quality of local institutions. A uniform approach is inadequate; a deeper understanding of local dynamics and policy responses is needed. This study integrates Agency Theory and Institutional Theory, and provides theoretical and practical contributions for managers and policymakers.